Edmodo: An Instructional Media to Teach English Grammar - Moh. Hanafi (STKIP PGRI Tulungagung, 2020)
This report aimed at measuring the effectiveness of Edmodo to teach English grammar. Edmodo as an online instructional media was used to teach English grammar. This research used quantitative approach with a pre experimental research design. The second semester students of English Department STKIP PGRI Tulungagung were taken as the sample of this study. Since there is no control group, the second semester students were assigned as the experimental group. One group pretest-posttest research design was used. From the analysis, it was found that the mean of the pretest was 59.47 and the mean of the posttest was 73.48. Based the test of assumptions, the data was found to be not parametric. So, the analysis using Wilcoxon test was used to test the hypothesis. The result the significant value (.027) was lower than level of significant .05. Therefore, it can be concluded that the students have significantly better grammatical mastery after being taught using Edmodo.